(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Evaluating erythropoietin (EPO) mRNA expression alongside conventional haematologic indices offers deeper insight into the body’s compensatory erythropoietic response. While most studies on blood donors focus on haemoglobin (Hb) and haematocrit (Hct), little is known about EPO gene expression, particularly among male donors who constitute the majority in many regions. This cross-sectional study assessed Hct, Hb, and EPO mRNA expression in 100 male donors in Ibadan, Nigeria (50 regular, 50 occasional). Haematological parameters were measured using automated methods, while EPO mRNA was quantified by GAPDH-normalised RT-PCR. Data were analysed using independent t-tests, Pearson’s correlation, and Mann–Whitney U tests at p<0.05 level of significance. Regular donors had significantly lower mean Hct (31.86±6.32%) and Hb (10.59±2.11 g/dL) compared to occasional donors (41.40 ± 3.30% and 13.77±1.10 g/dL; p<0.001). The EPO mRNA expression was more variable among regular donors, with 68% showing downregulation and 32% upregulation, whereas occasional donors had 10% downregulation and 90% upregulation (p = 0.905). The EPO mRNA and Hct showed a weak, insignificant correlation (r = 0.102, p = 0.315). Regular donors were more likely to exhibit subclinical anaemia, suggesting that Hb screening alone may not be sufficient to detect early haematologic stress and erythropoietic compensation. Occasional donors had higher EPO gene expression compared to regular donors, indicating they may be well-suited for blood donation due to their enhanced ability to regenerate red blood cells. These findings underscore the possibility of including molecular markers like EPO mRNA in donor monitoring to enhance donor safety and eligibility assessment.